Visual Identity Design of the “Berbagi Buahagia” Campaign on the Benefits of Fruit Consumption - Mochammad Sulthan Rajwa Atthariq; Pungky Febi Arifianto; Aryo Bayu Wibisono (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
Low fruit consumption among young adults in Indonesia remains a significant issue, with most individuals aged 18-25 not meeting recommended intake levels. This problem is influenced not only by limited awareness but also by ineffective health campaigns that lack engaging and relevant visual communication. This study aims to design the visual identity of the “Berbagi Buahagia” educational campaign to create a more effective and audience-centered communication strategy. The urgency of this research lies in addressing the gap between health campaign strategies and the application of visual communication design in influencing behavior among young adults in Indonesia today. This research uses a descriptive qualitative method with a field research approach. Data were collected through interviews, Focus Group Discussions (FGD), observations, and questionnaires involving selected participants. The design process applies the Design Thinking method, including empathize, define, ideate, prototype, and test stages. The results indicate that a well-designed visual identity with appealing visuals, consistent branding, and appropriate media can enhance audience engagement and message effectiveness. The campaign outputs include logo, digital media, posters, and supporting materials tailored specifically to young adults, encouraging healthier daily habits.